Gusto’so Pizzeria Restaurant / Muhammad Fahmi Hakimi Mohd Faizal ... [et al.] - Mohd Faizal, Muhammad Fahmi Hakimi; Mohamad Naser, Muhammad Haziq; Haslan, Muhammad Al-Amin; Mohd Firdaus How, Syahirul Nidham How; Zulkarnain, Khairunnizam (2021)
A Business Plan is a written document which described the proposed business or a project to be undertaken in a comprehensive manner which also known as a working paper, business proposal, project paper or prospectus. Based on the information gathered, for this task we have decided to plan a Business Plan about a Restaurant that sells Pizza called Gusto’so Pizzeria. Gusto’so Pizzeria is located at Tamarin Square in Cyberjaya. Tamarind Square is the premise is located at a very strategic area with an affordable rental rate which is one of the few reasons that was listed. Gusto’so is from the Italian word “Gusto” that means delicious. The pizza that our Trattoria serves is wood fired authentic pizza that are baked in the traditional Italian style oven with freshly made dough that are also made in house every day Gusto’so Pizzeria Nature of Business is Partnership formed within the people or specifically the Managers in the Business Plan that share the same interest and vision to open Gusto’so Pizzeria. The partners that are involved in this Business Plan contributed financially to start open the Gusto’so Pizzeria by invest money as it is expensive to venture into a new Business. They also helped in develop the Business Plan served as a Manager in the departments